Makna Simbolis dan Nilai Budaya dalam Upacara Adat Suku Abui di Kabupaten Alor - Marta Sriyanti Kaat; Miriam Oktorida Hingmo; Oya Feni B .Maulaka; Paskaria Asamai; Halena Muna Bekata (Pusat Riset dan Inovasi Nasional, 2025)
The research aims to describe the symbolic meaning and cultural values ​​in traditional ceremonies of the Abuy tribe, North Central Alor sub-district, West Lembur Village, Alor Regency. The Abuy traditional ceremony is the identity of West Lembur Village in general as a tourism process that must be preserved by the local community and is a tradition that still survives in the midst of modern progress like this. In this ceremony, there are various positions that are filled with symbolic meaning, such as a sarong woven cloth which has a moko motif which symbolizes the customs of marriage. This research uses a qualitative descriptive approach. Data was collected through direct observation through interviews with traditional shops and local communities. The research results show that this ceremony not only functions as a religious and social rite, but also as a medium for cultural preservation that strengthens community identity. Values ​​such as togetherness, gratitude and spirituality contained in this ceremony play an important role in maintaining social harmony and establishing human relationships with nature. Preserving this ceremony is important to maintain cultural heritage which has relevance in modern social life.